Induction of inflammatory cytokines by Nocardia fractions - Trebichavský, I; Barot-Ciorbaru, R; Charley, B; Splíchal, I (Folia biologica, 1993)
NDCM and NLD fractions of Nocardia opaca cell walls were used for in vitro stimulation of human and porcine peripheral blood mononuclear cells. Inflammatory cytokines IL-1, IL-6, tumour necrosis factor (TNF) alpha and interferon (IFN) gamma were detected at the single-cell level using paraformaldehyde-fixed and saponin-permeabilized mononuclears stained with cytokine-specific antibodies and indirect immunofluorescence method. IL-1, IL-6 and TNF were produced by human monocytes stimulated for 2 h, IFN gamma-positive lymphocytes were detected later. IFN gamma was produced also by activated porcine lymphocytes. Cells expressing apoptotic features were found among blood mononuclears treated with Nocardia fractions.
Keywords: Nocardia; fluorescenční protilátková technika; Cell Membrane Permeability; TNF-alfa; interferon gama; lidé; organické látky; miniaturní prasata; Fluorescent Antibody Technique; Humans; prasata; Interleukins; Tumor Necrosis Factor-alpha; monocyty; Animals; Cell Wall Skeleton; Monocytes; permeabilita buněčné membrány; zvířata; Swine, Miniature; interleukiny; skelet buněčné stěny; Mitogens; Lipopolysaccharides; mitogeny; Organic Chemicals; Interferon-gamma; lipopolysacharidy; Swine